The role of apoptosis in cell killing by cisplatin: a flow cytometric study - Ormerod, M G; Orr, R M; Peacock, J H (British journal of cancer, 1994)
Cell killing of L1210 cells by cisplatin has been studied using flow cytometry and DNA gel electrophoresis. Ten hours after a supralethal dose of drug (100 microM), extensive apoptosis was induced. Cells were also susceptible to the induction of apoptosis by nutritional deprivation, for example by incubation in arginine-deficient medium. After treatment in full medium with doses of drug in the range 1-10 microM, cells experienced a slow-down in S-phase transit followed by a G2 block. Cells either overcame the G2 block and continued to cycle or enlarged and eventually died. There was no evidence to suggest that cells dying from the G2 block underwent apoptosis. The data were consistent with a dual mechanism of cell death-higher doses of drug led to rapid death through apoptosis; lower doses led to death at later times resulting from failure to overcome a block in G2.